Emozioni: la vergogna - Miniati, Francesco (Studi sulla Formazione/Open Journal of Education, 2009)
The Author considers the shame as one of most important emotions because it talks about a complex inner world. It’s a diffuse thought the shame is tied to lot of imperfections but it usually is a faulty meaningful. So it’s not a failure but represents our need to be listened.